174k views
8 votes
3f^4g^3 x 8fg^4 / (6f^2g^3)^2 how do you do this?

User Alex Young
by
4.7k points

1 Answer

6 votes

9514 1404 393

Answer:

2/3·fg

Explanation:

The applicable rules of exponents are ...

(a^b)(a^c) = a^(b+c)

(a^b)/(a^c) = a^(b-c)

(ab)^c = (a^c)(b^c)

(a^b)^c) = a^(bc)

__

We assume your 'x' is a multiplication symbol, so you want to simplify ...


3f^4g^3 *( 8fg^4)/( (6f^2g^3)^2)\\\\=(3\cdot8f^(4+1)g^(3+4))/(6^2f^(2\cdot2)g^(3\cdot2))=(24)/(36)f^(5-4)g^(7-6)\\\\=\boxed{(2)/(3)fg}

User Al Zziwa
by
4.5k points